A novel case with germline p53 gene mutation having concurrent multiple primary colon tumours. (1st February 2003) - Miyaki, M; Iijima, T; Ohue, M; Kita, Y; Hishima, T; Kuroki, T; Iwama, T; Mori, T
Abstract : During a search for causative genes in patients with concurrent multiple primary colon tumours, we found a novel case with a germline mutation of the p53 gene, from GCC (Ala) to GTC (Val) at codon 189. Of the six primary colon tumours that this patient had, one large advanced carcinoma exhibited a somatic p53 mutation and a somatic APC mutation, in addition to the germline p53 mutation. Two early carcinomas and three adenomas had somatic APC mutations but no somatic p53 mutation or loss of the p53 allele. K-ras-2 mutations were detected in an advanced carcinoma and an early carcinoma. The present results suggest that a patient with a certain type of germline p53 mutation is predisposed to concurrent multiple colon tumours. It is also suggested that in such a patient, a somatic APC mutation is involved in tumour formation and that an additional somatic p53 mutation contributes to tumour progression.